KAJIAN ANALITIS DAN APLIKASI HEC-RAS DALAM PEMODELAN GERUSAN PADA PILAR JEMBATAN KURANJI KOTA PADANG - Elvi Roza Syofyan; Suhendrik Hanwar; Revalin Herdianto; Dalrino Dalrino (Jurnal Ilmiah Poli Rekayasa, 2026)
The Kuranji River Bridge is one of the important civil building infrastructures that was built to connect two roads that were cut off due to obstacles to the flow of the river. Bridges are useful as roads for vehicles to pass on them. In maintaining the function and ability of the bridge to serve traffic flow. Therefore, continuous inspection of the condition of the bridge must be an inseparable part of the system for maintaining bridge stability. The planned flood discharge in Batang Kuranji for return periods of 2 years, 5 years, 10 years, 25 years, 50 years, respectively, is 250.954 m3/s, 374.702 m3/s, 452.524 m3/s, 543,265 m3 /s, 623,773 m3 /s. The results of the analysis show that the bridge pillars and river flow cause scouring. The depth of scour that occurs on pillars using the analytical Lacey method and the HEC-RAS application for flood discharge for return periods of 2 years, 5 years, 10 years, 25 years, 50 years respectively is 1,756 m, 2,007 m, 2,138 m, 2,272 m, 2,379 m and 2,330 m, 2,460 m, 2,540 m, 2,600 m, 2,730 m. From the results of analytical calculations on flood discharge at a 50 year return period, the depth of scour is 2,379 m. Meanwhile, the maximum depth of scour from analysis using the HEC-RAS application is 2,730 m. This shows that the analytical calculation results are close to the HEC-RAS results.